ANALISIS BIG DATA PENJUALAN VIDEO GAMES MENGUNAKAN EDA - Daniel Ryan Hamonangan Sitompul; Ruben Ruben; Andreas Situmorang; Dennis Jusuf Ziegel; Julfikar Rahmad; Evta Indra; Davit Toramli Husni; Stiven Hamonangan Sinurat (Politeknik Bisnis Indonesia, 2022)
Advertising is a very effective way for product marketing, this method is often used to disseminate product information to be marketed. Errors in the analysis of products to be marketed resulted in significant losses to the company due to errors in the exploration of Big Data processing. Big data is described as large-scale data that can be presented, processed and analyzed using existing technologies, methods and theories. Therefore, an assessment of the big data of video game operators that is in demand by the market is carried out to determine the highest and lowest sales of video games using the Exploratory Data Analysis method so that a company can determine the games to be promoted and produced. The results obtained in this study that have the highest and lowest sales of video games in the global market by genre are action at 1745.27 and strategy at 174.5. And for sales by platform, PS2 is 1255.64 and PCFX is 0.03. With this method, video game sales can be presented graphically, making it easier for companies to determine which games to market and promote small game sales.